Scott and Bailey. Season one [videorecording (DVD)] - Anderson, Sarah Pia; Jones, Suranne, 1978-; Sharo, Lesley; Bullmore, Amelia, 1964- (BBC Worldwide Ltd. ; Warner Home Video Inc. [distributor], 2013)
Scott & Bailey is a thrilling investigative drama series exploring the personal and professional lives of two female detectives. Despite their differences, impulsive, funny and single Rachel and reflective, married mother-of-two Janet, have a great partnership. Thrown together in the toughest of murder cases, they have become the best of friends, ready to support each other both in and away from the incident room. Each episode sees Rachel and Janet face a serious crime that is both challenging and emotionally difficult, whilst coping with their complex personal lives. Scott and Bailey is an honest and powerful crime drama series. As seen on ABC1.